Marine-Derived Enterococcus faecalis HY0110 as a Next-Generation Functional Food Probiotic: Comprehensive In Vitro and In Vivo Bioactivity Evaluation and Synergistic Fermentation of Periplaneta americana Extract Powder - Feiyun Huang; Nan Yang; Qingqing Zhang; Cuiling Luo; Jingheng Wang; Yu Yang; Bisong Yue; Peng Chen; Xiuyue Zhang (Foods)
Addressing the escalating global burdens of inflammatory bowel disease and antimicrobial resistance demanded innovative food-based approaches to fortify gut health and suppress pathogens. We introduced a novel edible probiotic, Enterococcus faecalis HY0110, isolated from marine Thunnus thynnus. Through comprehensive in vitro, in vivo, and metabolomic analyses, we demonstrated its superior antibacterial effects compared to Lactobacillus rhamnosus GG, along with significantly enhanced antioxidant and free-radical scavenging capacities. Notably, elevated acetic acid production strongly correlated with its antimicrobial efficacy (R ≥ 0.999). HY0110 also exerted antiproliferative effects on HT-29 colorectal cancer cells by attenuating β-catenin and BCL-2 expression while upregulating pro-apoptotic markers P62 and c-PARP. In a DSS-induced colitis model, HY0110 alleviated inflammation, restored gut microbial homeostasis, and enhanced deterministic processes in community assembly dynamics. Furthermore, fermenting Periplaneta americana powder with HY0110 triggered extensive metabolic remodeling, notably a 668.73-fold rise in astragaloside A, plus increases in L-Leucyl-L-Alanine, S-lactoylglutathione, and 16,16-dimethyl prostaglandin A1. These shifts diminished harmful components and amplified essential amino acids and peptides to bolster immune modulation, redox balance, and anti-inflammatory responses. This work established a transformative paradigm for utilizing marine probiotics and novel entomological substrates in functional foods, presenting strategic pathways for precision nutrition and inflammatory disease management.